Resistin - concentrations in persons with type 2 diabetes mellitus and in individuals with acute inflammatory disease - Stejskal, David; Adamovská, Sylva; Bartek, Josef; Juráková, Renata; Prosková, Jitka (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2003)
UNLABELLED: Resistin is a recently discovered signal molecule, which could help elucidation of the pathophysiology of the insulin resistance and its correlation with obesity. As little information was available about resistin determination in venous blood at the time of our study, we focused on the question whether any correlation exists between persons with type 2 diabetes mellitus, with systemic inflammation, healthy persons and resistin concentrations and laboratory markers of inflammation, peptone, BMI. Differences of resistin values in these types of volunteers were studied as well. METHODS: Persons under study were divided into 3 groups: group A - with clinical signs of inflammatory disease of respiratory tract, leukocytosis > 10000/ul and CRP concentration > 50 mg/l (n = 35); group B - with well controlled type 2 DM treated by oral antidiabetic drugs, without clinical signs of inflammation and negative case history of acute disease (n = 12); group C - without clinical signs of inflammation and negative case history of acute disease (n = 77). For all volunteers we determined BMI index and examined resistin, leptin, interleukin 6, TNF-alpha, Na, K, Cl, insulin, cholesterol, HDL-cholesterol, LDL-cholesterol, triacylglycerols, creatinine, uric acid, ALT, AST, GMT, P, Mg and albumin in serum. RESULTS: Persons with clinical signs of severe inflammation had higher concentrations of Il6, CRP, resistin and a markedly lower BMI, decreased values of glucose, sodium, triacylglycerols, cholesterol, LDL-cholesterol and HDL-cholesterol compared to diabetics of type 2 (p < 0.05). Persons with clinical signs of severe inflammation showed significantly higher concentrations of TNF-alpha, Il6, CRP, resistin, glucose, leptin and considerably lower values of albumin, sodium and HDL-cholesterol than healthy individuals (p < 0.05). Persons with type 2 DM had markedly higher values of BMI, CRP, glucose, triacylglycerols, LDL-cholesterol, GMT and leptin, compared to healthy volunteers (p < 0.05). None of the three groups differed markedly in age or sex. Healthy volunteers show a significant correlation between leptin and resistin (correlation coefficient 0.82); this correlation was not found in patients with inflammation and type 2 DM. The group of volunteers with inflammations was found to have a significant positive correlation between resistin and inflammatory markers (correlation coefficient 0.3-0.5), negative correlation between resistin and cholesterol. We also found positive correlations between leptin and BMI as well as negative correlations between leptin and CRP. No significant correlations between resistin and other studied parameters were found in persons with type 2 DM. CONCLUSION: In healthy population a correlation was found between leptin and resistin concentrations in serum. In patients with severe inflammatory disease a correlation between resistin concentration and laboratory markers of inflammation was shown, however, no correlation was found between leptin and resistin. Resistin concentration in the serum of these patients is significantly higher ( p < 0.01) compared to healthy subjects and well controlled persons with type 2 DM with signs of insulin resistance. This may be due to a direct effect of inflammatory cytokines on resistin production. In persons with type 2 DM no significant correlations were found between resistin and other individual parameters ( insulin sensitivity markers, BMI or leptin). Resistin concentrations in persons with type 2 DM do not differ from concentrations of common population.
Keywords: leptin; Humans; lidé středního věku; Middle Aged; nemoci dýchací soustavy; akutní nemoc; Acute Disease; zánět; Resistin; mužské pohlaví; diabetes mellitus 2. typu; Leptin; C-reaktivní protein; Diabetes Mellitus, Type 2; Inflammation; ženské pohlaví; lidé; C-Reactive Protein; Respiratory Tract Diseases; Aged; resistin; senioři; Male; Female